Sexual Health Competencies for Undergraduate Medical Education in North America. Issue 4 (12th February 2017) - Bayer, Carey Roth; Eckstrand, Kristen L.; Knudson, Gail; Koehler, Jean; Leibowitz, Scott; Tsai, Perry; Feldman, Jamie L.
Abstract: Introduction: The number of hours spent teaching sexual health content and skills in medical education continues to decrease despite the increase in sexual health issues faced by patients across the lifespan. In 2012 and 2014, experts across sexuality disciplines convened for the Summits on Medical School Education and Sexual Health to strategize and recommend approaches to improve sexual health education in medical education systems and practice settings. One of the summit recommendations was to develop sexual health competencies that could be implemented in undergraduate medical education curricula. Aim: To discuss the process of developing sexual health competencies for undergraduate medical education in North America and present the resulting competencies. Methods: From 2014 to 2016, a summit multidisciplinary subcommittee met through face-to-face, phone conference, and email meetings to review prior competency-based guidelines and then draft and vet general sexual health competencies for integration into undergraduate medical school curricula. The process built off the Association of American Medical Colleges' competency development process for training medical students to care for lesbian, gay, bisexual, transgender, and gender non-conforming patients and individuals born with differences of sex development. Main Outcome Measures: This report presents the final 20 sexual health competencies and 34 qualifiers aligned with the 8 overall domains of competence. Results: Development of a comprehensive set of sexual health competencies is a necessary first step in standardizing learning expectations for medical students upon completion of undergraduate training. Conclusions: It is hoped that these competencies will guide the development of sexual health curricula and assessment tools that can be shared across medical schools to ensure that all medical school graduates will be adequately trained and comfortable addressing the different sexual health concerns presented by patients across the lifespan.